Financing the Future: An Argument for a Parallel Optional Currency - Stefan Brunnhuber (Global Labor Organization (GLO), 2017)
This talk aims to provide an argument for a parallel, optional, complementary currency system in order to overcome the constraints of the global economy and finance social and ecological projects on a global level. This argument goes beyond regulatory efforts and co-financed redistribution. The advantages of implementing this or a similar mechanism are manifold: firstly, it can be implemented in a fast and targeted manner and is relatively cheap. Secondly, it would have an anticyclical, antiinflationary and resilient impact on our trading and payment system. Thirdly, it builds on findings in systems theory, thus avoiding the tedious discussion between the different schools of economics. Fourthly, it addresses the magnitude, volume and significance of the global challenges ahead. In short: this argument is based on a new kind of thinking on how to design a monetary ecosystem to make the world a better place.
Keywords: 330; Sustainable Development Goals (SDGs); financing global commons; parallel optional currency